The professional development of higher education-based teacher educators: needs and realities - MacPhail, Ann; Ulvik, Marit; Guberman, Ainat; Czerniawski, Gerry; Oolbekkink-Marchand, Helma; Bain, Yvonne (Professional Development in Education, 2019)
Current literature suggests that while teacher educators perform a multitude of complex roles, they receive minimal preparation or possibilities for professional development to fulfil these roles. As a result, they need to acquire relevant knowledge and skills after taking on the position of teacher educators. Therefore, it is important to learn what skills and knowledge teacher educators need and how they acquire such skills and knowledge throughout their career. The purpose of this study is to describe the professional development needs and activities of 61 teacher educators across six national jurisdictions (England, Ireland, Israel, Norway, Scotland and The Netherlands) and to reveal influencing factors and affordances conducive to professional development. Semi-structured interviews constituted questions on professional learning opportunities and teacher education and research. Results from the interviews convey themes around the areas of (i) self-initiated professional development, (ii) the importance of experiencing professional development through collaboration with peers and colleagues, (iii) accessing opportunities to improve teacher education teaching practices, and (iv) the inextricable link between teaching and research and, consequently, the need to upskill in research skills. Discussion points that arise include the induction period, frustration and tension in navigation, haphazard professional learning and learning with, and from, each other.
Publisher: Routledge _eprint: https://doi.org/10.1080/19415257.2018.1529610
Keywords: Teacher educators; professional development; professional learning